The spread of branch banking and the demand for cash in post-war Germany - Malte Krueger (Research On Money in the Economy (ROME), 2016)
The period from the 1950s to the late 1970s saw an almost uniform decline of cash-to-GDP ratios in industrial countries. A closer look at the German payment system suggests that the factor causing such a change has been the shift towards cashless wage payments. In this period, in Germany, the branch network of the banks expanded significantly and at the end of the period almost all economically active persons had a current account. This change was triggered by rising wages and incomes. Rising wages increased the burden of weekly wage payments in cash, and rising incomes made the average earner more interesting for banks. Moreover, regulation and de-regulation, triggering both, price and non-price competition, may also have played a role. Technological change has not been an independent driver. The introduction of cashless wage payments has not only affected the payment behavior but also the savings behaviour of households. These changes were evolutionary rather than revolutionary, however. So, even though the cash-to-GDP ratio declined in this period, absolute amounts of real cash per capita were still rising.
Keywords: E41; G29; L89; O33; 330; retail payments; demand for cash; innovation